Artificial Intelligence and Attitudes towards Research in University Students - Calizaya-Lopez, José; Carita-Choquecahua, Ariosto; Barreda-Coaquira, Ana; Condori, Silvana Petronila Chata; Flores, Magdalena Marleni Marroquin; Aleman-Vilca, Yaneth (Journal of Posthumanism, 2025)
Artificial intelligence (AI) is transforming education and academic research by providing advanced tools for the search and analysis of information. This situation has changed the way university students access knowledge and research projects are developed. The aim was to determine the relationship between the use of AI and attitudes towards research in university students, according to socio-academic variables. The study was non-experimental, cross-sectional, quantitative and correlational. 2336 university students from a public university and three private universities from a town in Peru participated, intentionally chosen. A high level of AI use was found in 85.6% of students and unfavorable attitudes towards research in 46%. Likewise, the variables are not significantly related (p>0.05), therefore, attitudes towards research are explained by other variables. It´s concluded, the absence of a significant relationship between the use of AI and attitudes towards research indicates that the availability of technological tools is not sufficient to motivate research interest in university students.